(untitled) (Research, Society and Development, 2021)
The study presents the knowledge about electronic waste (WEEE) being a case study of students from IFPA campus parauapebas, the article aims to analyze the knowledge of students about electronic waste and produce a prototype of the point of collection of electronic waste. Electro-electronic waste is discarded waste with its final useful life. In the composition of these materials, dangerous metals are found that are difficult to decompose and with a great potential to harm the environment. some corner of the house, but they are recyclable and can become raw material. The collection point can become a great ally in the search for suitable places for waste, however the lack of awareness of a large part of the population about the places necessary for the care of this waste is a problem in the current reality caused by the intense increase of the population. and technological advancement. Thus, the importance of creating a prototype with a WEEE collection point for the campus was identified, valuing the colors of the IFPA campus and facilitating the understanding of the target audience on the subject. The results achieved through the analysis and responses of the questionnaires had in mind that there was already an environmental awareness about these residues, however on the campus there is no collection point and some courses such as Electro-electronics were shown to be below average in relation to knowledge about the importance of WEEE. According to the results of the article, the importance of environmental awareness among students on the Parauapebas campus is shown, which can be done with more disciplines focused on the environment in the various courses, such as the creation of lectures with the entire academic community.